2022
DOI: 10.5194/egusphere-egu22-5277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-instrumental investigation of the solar flares impact on the ionosphere occurring in December 2006

Abstract: <p>The sudden increase of X-radiation and EUV emission following solar flares causes additional ionization and increased absorption of electromagnetic (EM) waves in the sunlit hemisphere of the Earth’s ionosphere. The solar flare impact on the ionosphere above Europe on 05 and 06 December 2006 was investigated using ground-based (ionosonde and VLF) and satellite-based data (Vertical Total Electron Content (VTEC) derived from Global Navigation Satellite Systems (GNSS) observations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In parallel, if we look through the variation of the fmin parameter we can not recognise any changes of the diurnal pattern in connection with the geomagnetic storm, only the increased values at the time of the flare events are clear. It agrees well with the findings of previous studies, e.g., Barta et al, 2022, that the fmin parameter is sensitive to the changes caused by the solar flares, while the foF2 parameter can show the variation caused by the dynamical changes in the thermosphere-ionosphere (F-region) system during geomagnetic storms.…”
Section: Jrsupporting
confidence: 92%
See 4 more Smart Citations
“…In parallel, if we look through the variation of the fmin parameter we can not recognise any changes of the diurnal pattern in connection with the geomagnetic storm, only the increased values at the time of the flare events are clear. It agrees well with the findings of previous studies, e.g., Barta et al, 2022, that the fmin parameter is sensitive to the changes caused by the solar flares, while the foF2 parameter can show the variation caused by the dynamical changes in the thermosphere-ionosphere (F-region) system during geomagnetic storms.…”
Section: Jrsupporting
confidence: 92%
“…However, these large flares caused long-lasting total radio blackouts at all stations, thus we had detected signals only 30-120 min after the peak time. Nevertheless, the computed Ne changes are ∼100% at 74 km after C4.8-C5.1 class flares (Srećković et al, 2021;Barta et al, 2022) which agree with the changes (68%-102%) observed at 2.5 MHz after the C8.3 flare on 04 September, when there was no total radio blackout.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations